Morphologic Examination of Ossicula Auditus in Different Ruminants - İsmail Demircioğlu; Funda Aksünger Karaavci (Veterinary Medicine and Science)
ABSTRACT Background The ossicula auditus is the structure that transmits vibrations from the tympanic cavity to the auris interna. This assembly is formed by three ossicles: the malleus, incus and stapes. In addition, the bone that exists as os lenticulare in humans exists as processus lenticulare in most mammals. Objective To our knowledge, no in‐depth study has been published on the ossicula auditus of gazelles. This study aims to provide a comparative study of the morphology of the auditory ossicles in sheep, goats and gazelles. Methods Ossicula auditus from six adult Awassi sheep, six hair goats and six gazelles was examined and photographed under a stereomicroscope. Results and conclusion It was determined that the ossicula auditus of gazelle, hair goat and Awassi sheep consisted of malleus, incus and stapes. In the species examined, it was observed that the articular surface on the caput mallei, the malleus protrusions and the distal part of the manubrium mallei differed between species. It was determined that the incus bone consists of a body and two crus. As an important morphological difference, the proc. lenticulare was found to be on the crus breve in all three species. It was determined that the stapes bone was quadrangular in the species examined, especially in goats, but this quadrangular shape, which is specific to ruminants, was not fully formed in other species. As a result, it was determined that the ossicula auditus of gazelle, hair goat and Awassi sheep showed morphologically different characteristics.